Pengaruh Pertumbuhan Ekonomi, Pengangguran dan Indeks Pembangunan Manusia Terhadap Kemiskinan di Provinsi Kalimantan Tengah - Syahriah Syahriah; Alexandra Hukom (Manajemen Kreatif Jurnal, 2023)
The purpose of this study is to identify and analyze the impact of economic growth, unemployment and the Human Development Index on poverty levels in Central Kalimantan. Survey data is a quantitative research method using a descriptive data approach and can be obtained from search engines such as BPS and other online data providers. There is a correlation between the Human Development Index (IPM) and the poverty rate in Central Kalimantan Province which shows that the poverty rate increases with every increase in the HDI. Estimates for other causes are constant. In addition, to reduce unemployment through vocational training programs, increase the transfer of personal wealth or human resources needed to build infrastructure to increase employment and provide them with social support